Endometrial telomerase activity in women with either endometrial cancer or hyperplasia: A systematic review and meta-analysis - Pérez-López, Faustino R. (2023)
Aim: We performed a systematic review and meta-analysis to assess whether endometrial telomerase activity is associated with endometrial cancer or hyperplasia. Methods: PubMed, Web of Science, Embase, Scielo, LILAC, and CNKI databases were searched to obtain relevant literature for articles published through June 2022, following PRISMA guidelines and a registered PROSPERO protocol. We included observational studies reporting endometrial telomerase activity in patients with either endometrial cancer or hyperplasia compared with benign endometrial tissue (control women). The Newcastle-Ottawa Scale was used to evaluate the quality of studies. Data were expressed as the odds ratios (OR) and 95 % confidence intervals (CI). Random effects and inverse variance methods were used to meta-analyze associations. The I2 test was used to assess heterogeneity. Results: There were significant associations between endometrial telomerase activity and either endometrial cancer (20 studies, OR = 10.65, 95 % CI 6.39, 17.75, p = 0.00001, I2 = 21 %) or endometrial hyperplasia (nine studies, OR = 3.62, 95 % CI 1.61, 8.13, p = 0.002, I2 = 36 %) compared to women without endometrial cancer and hyperplasia. There was not a significant difference in telomerase activity in women with endometrial cancer compared to those with endometrial hyperplasia (seven studies, OR = 1.03; 95 % CI 0.31, 3.37, p = 0.96, I2 = 49 %). In subgroup analyses, there were no significant differences in telomerase activity in patients with endometrial cancer by type of observational studies and by countries of the studies. Conclusion: Endometrial telomerase activity is higher in women with either endometrial cancer or endometrial hyperplasia compared to control women without those lesions.